2010
DOI: 10.1016/j.socscimed.2010.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Marital status and gender differences in managing a chronic illness: The function of health-related social control

Abstract: The attempts of social network members to regulate individuals' health behaviors, or health-related social control, is one mechanism by which social relationships influence health. Little is known, however, about whether this process varies in married versus unmarried individuals managing a chronic illness in which health behaviors are a key component. Researchers have proposed that social control attempts may have dual effects on recipients' well-being, such that improved health behaviors may occur at the cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
156
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(181 citation statements)
references
References 38 publications
17
156
0
8
Order By: Relevance
“…Thus, perceptions and functions of social relations are more strongly associated with emotional burden than is the structure of the social relations. This finding is supported by previous research in people with chronic illness [35][36][37].…”
Section: Discussionsupporting
confidence: 89%
“…Thus, perceptions and functions of social relations are more strongly associated with emotional burden than is the structure of the social relations. This finding is supported by previous research in people with chronic illness [35][36][37].…”
Section: Discussionsupporting
confidence: 89%
“…Hence marital status is a significant confounding variable for albuminuria, which needs to be looked into while designing a model for the home based care for the diabetics. A finding which is in agreement with August et al who observed that within the social support network, the spouse is the most important source of support on matters relating to health management especially dietary and treatment adherence [14]. Similarly, significant difference was found with regard to duration of diabetes, HDL-C levels, and blood pressure (systolic and diastolic).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, greater accumulations of BRF combinations occurred among individuals who were living with a partner, contrary to what was found in another study, in which this characteristics was a protective factor. 1 Although age, race and sex cannot be modifi ed, the majority of the risk factors relate to lifestyle and behavioral patterns that can be modifi ed. A variety of interventions aimed at reducing BRFs have been implemented over recent decades.…”
Section: Discussionmentioning
confidence: 99%